LEGAL BASIS FOR THE DEVELOPMENT OF HIGHER EDUCATION CURRICULUM BASED ON LAW NO. 12 OF 2012 ON HIGHER EDUCATION - Gunawan Widjaja (Adisam Publisher, 2025)
This study discusses the legal basis for the development of higher education curricula based on Law No. 12 of 2012 on Higher Education. This study examines the legal provisions governing the formulation and development of curricula in order to ensure the quality, relevance, and sustainability of higher education in Indonesia. The results of the study indicate that Law No. 12 of 2012 provides a strong and comprehensive legal basis for higher education institutions to develop curricula that are in line with national standards and national development needs. In addition, this law regulates the rights and obligations of higher education institutions in developing holistic, adaptive curricula that are oriented towards learning outcomes covering attitudes, knowledge, and skills. The implications of this legal basis encourage higher education institutions to implement a high-quality, character-building curriculum that is competitive at the national and international levels.